Dielectric properties of chickpea, red and green lentil in the microwave frequency range as a function of temperature and moisture content. Issue 3 (3rd July 2018) - Taheri, Saeedeh; Brodie, Graham; Jacob, Mohan V.; Antunes, Elsa
ABSTRACT: Dielectric properties are essential for application in: thermal processes using microwave and radio frequency; predicting heat uniformity in dielectric heating; and developing moisture measurement equipment based on electromagnetic waves. While the dielectric properties of many agricultural legumes have been studied, their response as a function of moisture content and temperature at microwave frequencies has not been well explored. In this study, dielectric properties of Kabuli chickpea, green and red lentils were measured, using an open-ended coaxial probe, at four moisture contents between 8% and 20% wet base (wb), temperatures up to 80 °C and in the microwave frequency range of 700–7000 MHz, which includes three allowed frequencies of 915, 2450, 5800 in the Industrial, Scientific and Medical microwave range. According to the results, at frequencies above 3000 MHz, there is a negative linear relation between loss factor and frequency and the linearity was more at higher moisture contents. Due to the linear correlation of the complex-plane plot, legumes' densities could be predicted from their dielectric properties at 1800 MHz. At 2450 MHz, penetration depths at room temperature are below 5 and 15 cm for chickpea kernels and powdered lentils, respectively. Therefore, chickpeas need to be treated in one layer during microwave processing for more heat uniformity.